Advanced reduction process to achieve efficient degradation of pyridine. (January 2022) - Liu, Shuhao; Han, Jinglong; Ding, Yangcheng; Gao, Xiaoxu; Cheng, Haoyi; Wang, Hongcheng; Liu, Chunshuang; Wang, Aijie
Abstract: Pyridine and its derivatives are widely consumed and detected in the environment persistently, which can cause potential adverse impacts on environment and human health. Considering the fact that pyridine could absorb UV light at 254 nm to generate excited one, which could react with reductive radicals, promoting its structural changes, we proposed that one typical efficient advanced reduction process (ARP) which combines UV irradiation with sulfite could be used to eliminate pyridine quickly. Sulfite/UV process showed a higher pyridine removal rate with a pseudo-first-order reaction rate constant of 0.1439 min −1, which was 3 times of that in UV irradiation and 1.3 times in UV/H2 O2 process. This was primarily due to reductive radicals (eaq –, H and SO3 – ) produced by UV irradiation. The removal rate of pyridine was highest in slightly alkaline environment. And the presence of oxygen, as well as certain concentration of humid acid just showed slight inhibition, indicating the possibility of application in practical environment. A positive impact was observed with increasing sulfite dosage, but it was gradually inhabited when the dosage was over 5 mM. The present study may provide an alternative efficient technology for the degradation of pyridine ring-containing substances. Graphical abstract: Image 1 Highlights: Direct UV irradiation and reductive radicals enhanced the degradation of pyridine. Sulfite/UV process showed a higher degradation efficiency of pyridine. The removal rate was highest in the environment of pH 8.2 with 2.5 mM sulfite. The presence of oxygen or HA just showed slight inhibition.